(untitled) (diségno, 2026)
Graphic statics is a structural calculation method derived from the concept of the thrust line and used by Catalan Modernism. A disciple of Antoni Gaudí, Cèsar Martinell, employed it in the design of 15 wineries between 1918 and 1922, which are now known as cathedrals of wine. One of them, the Pinell de Brai winery, illustrates the transformation of an initially projected structure with wooden trusses into one using masonry arches, which is the object of this study. By analyzing eight of the sketches using a graphic restitution methodology, it is possible to compare the masonry arches to the shapes of the catenary and the parabola, with an ac- curacy of ± 0.077 m for scale 1:100, and ± 0.052 m for scale 1:50. This analysis has made it possible to determine how the design process was developed: from trusses, to structural definition through trial and error using architectural drawing with graphic statics, and finally, the executed project featuring tied arches. In conclusion, none of the 14 drawn arches is strictly parabola or a catenary. The eight arches of the central nave tend toward the catenary shape, while the smaller-span arches of the side naves tend toward the parabola. The four masonry arches in the final project were drawn through point transposition using an auxiliary construction with a hanging chain, where the architectural structure was resolved using graphic methodologies.